Malaysia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Authorities of Malaysia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights the Malaysian economy's good performance over the past few years in a challenging global economic environment. Despite the impact of global commodity price and financial market volatility, the economy remained resilient, thanks to a diversified production and export base, strong balance sheet positions, a flexible exchange rate, responsive macroeconomic policies, and deep financial markets. Although real GDP growth slowed, Malaysia is still among the fastest-growing economies among its peers. Real GDP growth is expected to increase moderately to 4.5 percent year over year in 2017 from 4.2 percent in 2016. Domestic demand, led by private consumption, continues to be the main driver of growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet